Answer:
R = -S - rR
Step-by-step explanation:
S = R - rR
R = -S - rR
Answer:
2
Step-by-step explanation:
<u>Given AP where:</u>
<u>To find</u>
<u>Since</u>
- a₄ = a₁ + 3d
- a₂ = a₁ + d
- a₆ = a₁ + 5d
<u>Initial equations will change as:</u>
- a₁ + 3d = 2(a₁ + d) - 1 ⇒ a₁ + 3d = 2a₁ + 2d - 1 ⇒ a₁ = d + 1
- a₁ + 5d = 7 ⇒ a₁ = 7 - 5d
<u>Comparing the above:</u>
- d + 1 = 7 - 5d
- 6d = 6
- d = 1
<u>Then:</u>
- a₁ = d + 1 = 1 + 1 = 2
- a₁ = 2
The first term is 2
Answer:
A
Step-by-step explanation:
We can substract the wavength of the violet light to the wavelength of the red light:
(6.5 x 10^-7 m) - (4.0 x 10^-7 m) = 2.5 x 10^-7 m
Answer:
$1596
$1597.28
$1598.33
bank A
Step-by-step explanation:
The formula for calculating compound interest:
FV = P (1 + r/m)^mn
FV = Future value
P = Present value
R = interest rate
N = number of years
m = number of compounding
Bank A = $1500(1.064) = $1596
Bank B = $1500( 1 + 0.063/12)^12 = 1597.28
Bank C = $1500( 1 + 0.0635/365)^365 = $1598.33
Bank A pays the least amount of interest